Swedish year one teachers’ perspectives on homework in children’s learning of number: an ongoing controversy - Petersson, J; Marschall, G; Sayers, J; Andrews, P (Swedish Society for Research in Mathematics Education, 2018)
This paper draws on semi-structured interviews undertaken with twenty teachers of year one children in Sweden. Interviews focused on teachers’ construal of their own and their pupils’ parents’ roles in supporting year one children’s learning of early number. Data, which were analysed by means of a constant comparison process, yielded homework as a theme that dichotomised teachers between those who set homework for learning number and those who do not. Of those who set homework, the majority construed it as a means of facilitating number-related fluency, particularly for children in danger of falling behind their peers. Of those who do not, the majority argued that differences in family backgrounds would compromise societal principles of equality of opportunity